Smart calling : eliminate the fear, failure, and rejection from cold calling - Sobczak, Art (Wiley, 2013)
This book provides tips and techniques for effective cold calling. It reflects changes and advances in the information gathering that comprises the "smart" part of the calling, and also includes real-life examples and success stories.